Internet-Based Cognitive Behavioral Therapy for Children and Adolescents With Dental or Injection Phobia: Randomized Controlled Trial - Robert Schibbye; Erik Hedman-Lagerlöf; Viktor Kaldo; Göran Dahllöf; Shervin Shahnavaz (JMIR Publications, 2024)
BackgroundDental phobia (DP) and injection phobia (IP) are common in children and adolescents and are considered some of the biggest obstacles to successful treatment in pediatric dentistry. Cognitive behavioral therapy (CBT) is an evidence-based treatment for anxiety and phobias. As the availability of CBT in dentistry is low, internet-based CBT (ICBT) was developed. Open trials have shown that ICBT is a promising intervention, but randomized trials are lacking. ObjectiveThis randomized controlled trial tests whether therapist-guided ICBT supported by a parent could reduce fear, allowing children and adolescents with DP or IP to receive dental treatment. MethodsWe enrolled 33 participants (mean age 11.2, SD 1.9 y) whom a clinical psychologist had diagnosed with DP, IP, or both. After inclusion, participants were randomized to either ICBT (17/33, 52%) or a control group of children on a waitlist (16/33, 48%). ICBT was based on exposure therapy and comprised a 12-week at-home program combined with visits to their regular dental clinic. Participants corresponded weekly with their therapist after completing each module, and 1 parent was designated as a coach to support the child in the assignments during treatment. All participants completed measurements of the outcome variables before treatment start and after 12 weeks (at treatment completion). The measurements included a structured diagnostic interview with a clinical psychologist. Our primary outcome measure was the Picture-Guided Behavioral Avoidance Test (PG-BAT), which assesses the ability to approach 17 dental clinical procedures, and a positive clinical diagnosis. Secondary outcome measures included self-report questionnaires that measured self-efficacy and levels of dental and injection anxiety. The children and their parents completed the questionnaires. ResultsAll participants underwent the 12-week follow-up. After treatment, 41% (7/17) of the participants in the ICBT group no longer met the diagnostic criteria for DP or IP, whereas all participants in the control group did (P=.004). Repeated-measure ANOVAs showed that ICBT led to greater improvements on the PG-BAT compared with the control group; between-group effect sizes for the Cohen d were 1.6 (P<.001) for the child-rated PG-BAT and 1.0 (P=.009) for the parent-rated PG-BAT. Reductions in our secondary outcomes-dental fear and anxiety (P<.001), negative cognitions (P=.001), and injection fear (P=.011)-as well as improvements in self-efficacy (P<.001), were all significantly greater among children in the ICBT group than in the controls. No participants reported adverse events. ConclusionsICBT seems to be an effective treatment for DP and IP in children and adolescents. It reduced fear and anxiety and enabled participants to willingly receive dental treatment. ICBT should be seriously considered in clinical practice to increase accessibility; this therapy may reduce the need for sedation and restraint and lead to better dental health in children and adolescents. Trial RegistrationClinicalTrials.gov NCT02588079; https://clinicaltrials.gov/study/NCT02588079